Guild-Ridden Labor Markets : The Curious Case of Occupational Licensing - Kleiner, Morris M. (Book collections on Project MUSE., 2015)
Kleiner examines why the institution of occupational licensing has had such a curious evolution and influence in the United States, the European Union, and China. He also discusses the many similarities it has to guilds.